2015
DOI: 10.1007/s00246-015-1196-3
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete RV Remodeling After Transcatheter ASD Closure in Pediatric Age

Abstract: Published data showing the intermediate effect of transcatheter device closure of atrial septal defect (ASD) in the pediatric age-group are scarce. The objective of the study was to assess the effects of transcatheter ASD closure on right and left ventricular functions by tissue Doppler imaging (TDI). The study included 37 consecutive patients diagnosed as ASD secundum by transthoracic echocardiography and TEE and referred for transcatheter closure at Cairo University Specialized Pediatric Hospital, Egypt, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This study demonstrated reverse of remodeling both RV and LV using STE after transcatheter ASD closure in children. The assessment of ventricular function following percutaneous ASD closure is complicated by the alteration to loading conditions caused by the elimination of intracardiac shunting [ 8 ]. Adverse ventricular interdependence associated with RV volume overload was previously described as “Bernheim effect”, in which the interventricular septum bulges into the LV cavity and leads to impairment of LV filling [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated reverse of remodeling both RV and LV using STE after transcatheter ASD closure in children. The assessment of ventricular function following percutaneous ASD closure is complicated by the alteration to loading conditions caused by the elimination of intracardiac shunting [ 8 ]. Adverse ventricular interdependence associated with RV volume overload was previously described as “Bernheim effect”, in which the interventricular septum bulges into the LV cavity and leads to impairment of LV filling [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, by TDI, LVMPI significantly improved as well as the peak systolic velocity of LV lateral wall increased after device closure. This finding might be explained by the restoration of LV compression and the increase in LV filling [ 8 ]. Furthermore, Raymond et al [ 27 ] concluded that the LV geometry is altered with mild impairment of LV filling and decrease in LV dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both studies demonstrated preservation of right ventricular function. However, the RV contraction takes time to recover completely after eliminating a left‐to‐right shunt . Additionally, the permanent implantation of an occluder in the atrial septum may acutely influence the RV contraction postprocedure, particularly in younger children …”
Section: Introductionmentioning
confidence: 99%
“…17 The time course of cardiac remodelling in the literature has a broad range from 3 months 29 to 2 years. 30 In one study on children weighing less than 10 kg, the RV dimensions and the RV/LV proportion gradually decreased and normalised in the first year after the PTC. 28 On the other hand, in a recent study on the evaluation of RV myocardial strains after PTC of secundum ASD in children, the researchers showed that the intervention improved the RV strain indices and RV function normalised in 3 months.…”
Section: Discussionmentioning
confidence: 99%